Our struggle for self ; Coming to Palawan ; Discovering Guimaras [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Summary: Documents the Asia-Pacific Conference on East Timor; the migration of people in Palawan; and the mango plantation in Guimaras, Iloilo.